PENINGKATAN HASIL BELAJAR IPS SISWA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI SD - Nur, Astuti; Zuardi, Zuardi; Yunisrul, Yunisrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this study is to describe the improvemen of sudent learning outcomes on learning IPS by using model prolem based learning in the classroom IV SD Negeri 09 Talang Babungo on the student class IV who number 22 students. This research uses qualitative and quantitative  approach. The type of research in clssroom action research student learning outcomes cycle 1 83,7 increase to 86,6 in cycle 2. Thus, the prolem based learning model can improve sudent learning outcomes in IPS learning in grade IV SD Negeri 09 Talang Babungo Keywords: ips, Problem Based learning.